1984
DOI: 10.1007/bf01338727
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of diabetes and glaucoma in a rural North Carolina community

Abstract: Effective use of time, money, and personnel in the delivery of health care services to rural areas requires baseline information on the target population with respect to the problem being addressed. Prior to the initiation of an educational program on diabetes and glaucoma, the Public Health Department of Davie County, North Carolina, conducted a survey of county residents to determine knowledge, attitudes, and practices concerning these illnesses. The goals of the survey were to determine (1) basic knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 5 publications
1
20
1
Order By: Relevance
“…10 14 Pronzato et al  14 also found that women and patients with a higher education level were more knowledgeable about their disease. Michielutte et al  12 found that females and people who reached higher levels of education had the highest levels of knowledge of glaucoma and diabetes. Researchers of the Lighthouse National Survey10 found that the youngest, wealthy, and more educated respondents were more likely to be informed about visual impairment.…”
Section: Discussionmentioning
confidence: 99%
“…10 14 Pronzato et al  14 also found that women and patients with a higher education level were more knowledgeable about their disease. Michielutte et al  12 found that females and people who reached higher levels of education had the highest levels of knowledge of glaucoma and diabetes. Researchers of the Lighthouse National Survey10 found that the youngest, wealthy, and more educated respondents were more likely to be informed about visual impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Various population-based studies have shown that awareness and knowledge of glaucoma among both rural and urban populations is low in developed countries [8][9][10][11][12][13] and worse in developing countries. 8,[14][15][16][17][18] Unfortunately, in Ghana and many other parts of Africa, eye-care services are provided and managed mainly by a few trained eyecare professionals.…”
mentioning
confidence: 99%
“…Others have demonstrated that increasing patients' knowledge about their disease and "tailoring" the therapeutic regimen into the patients' daily life effectively increased correct usage of medication (5)(6)(7)(8)(9)(10) . It has been reported that glaucoma patients have little understanding of their disease and its treatment (2)(3)(4)(11)(12) , but there are few studies assessing this information directly. In a previous study, some of us reported that the Purpose: To evaluate the knowledge glaucoma patients have about their disease and its treatment.…”
Section: Introductionmentioning
confidence: 99%